Schiff's bases of quinazolinone derivatives: Synthesis and SAR studies of a novel series of potential anti-inflammatory and antioxidants. Issue 5 (1st March 2015) - Rakesh, K.P.; Manukumar, H.M.; Gowda, D. Channe
Graphical abstract: Abstract: A series of quinazolinone derived Schiff base derivatives7 –28 were synthesized and characterized as novel antioxidants and anti-inflammatory agents. The in vitro antioxidant activities of these compounds were evaluated and compared with commercial antioxidants ascorbic acid (AA), gallic acid (GA), butylatedhydroxytoluene (BHT), butylatedhydroxyanisole (BHA) employing 1, 1-diphenyl-2-picryl-hydrazyl (DPPH) assay, 2, 2-azinobis-(3-ethylbenzothiazoline-6-sufonic acid) (ABTS) assay and N, N -dimethyl- p -phenylenediamine dihydrochloride (DMPD) assay. The results revealed that IC50 of17, 18, 23, 24, 25, 27 and28 were lower than the IC50 of standards in all the three performed antioxidant assays indicating good activities of these compounds. In addition, in vitro anti-inflammatory activity of the synthesized compounds were evaluated and the results demonstrate that the compounds9 –12 exhibited excellent anti-inflammatory activity. Preliminary structure–activity relationship revealed that the compounds17, 18, 23, 24, 25, 27 and28 with electron donating moiety (OH, OCH3 ) were found to be excellent antioxidants and compounds9, 10, 11 and12 with electron withdrawing moiety (Cl, NO2 ) were found to be excellent anti-inflammatory agents.